2015
DOI: 10.3109/09638288.2015.1036174
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different initiation time of exercise training on left ventricular remodeling and cardiopulmonary rehabilitation in patients with left ventricular dysfunction after myocardial infarction

Abstract: Early exercise training is safe and feasible in acute and healing phase after myocardial infarction. Early exercise training could attenuate LV remodeling and improve cardiopulmonary capacity in patients with myocardial infarction after hospital discharge (around one week post-MI). Exercise training has favorable effects on LV remodeling and cardiopulmonary capacity rehabilitation. Exercise training should be treated to have the same roles with drugs in secondary prevention of myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 47 publications
1
41
0
4
Order By: Relevance
“…Previous studies have shown that patients with LV systolic dysfunction benefit more from CR. 22 The number of ACS patients undergoing CR was low for various reasons, as analyzed in previous studies, including financial constraints, difficulties in transportation, conflicts with work, low motivation and geographic distance. There are multiple barriers to CR, three of which have been identified as patient-related, physician-related and health system-related factors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that patients with LV systolic dysfunction benefit more from CR. 22 The number of ACS patients undergoing CR was low for various reasons, as analyzed in previous studies, including financial constraints, difficulties in transportation, conflicts with work, low motivation and geographic distance. There are multiple barriers to CR, three of which have been identified as patient-related, physician-related and health system-related factors.…”
Section: Discussionmentioning
confidence: 99%
“…To demonstrate the connections between an albatross plot and established techniques, we first illustrate the albatross plot using a data set that was originally analysed using effect sizes and which could, therefore, be illustrated in a forest plot. Zhang et al performed a meta‐analysis of randomized trials evaluating the effect of exercise training after an acute MI . They examined the endpoint of left ventricular function (LVEF), subgrouping the trials by the period after the MI during which exercise training was initiated.…”
Section: Applicationsmentioning
confidence: 99%
“…Forest plot of studies of the effect of exercise training on left ventricular fraction after acute myocardial infarction, data from Zhang et al I‐V subtotals represent fixed effect meta‐analyses; D+L subtotals represent random effect meta‐analyses. I‐squared is a relative measure of heterogeneity in relation to total variability within each subgroup.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a population diagnosed with myocardial infarction, early-initiated exercise in the acute phase has shown greater benefits on exercise capacity than is the case in exercise interventions initiated in a later treatment phase (11). Systematic reviews investigating the effects of preand post-surgical exercise interventions in patients with NSCLC show that exercise may increase exercise capacity of people following lung resection for NSCLC (6,12,13).…”
mentioning
confidence: 99%